Open source geographical resources analysis support system (GRASS) for landslide hazard assessment - Ramli, Mohammad Firuz; Sulaiman, Wan Nor Azmin; Yusoff, Mohd Kamil; Yoke, Yee Low; Abd. Manap, Mohamad (Emerald Group Publishing Limited, 2005)
Purpose – The primary aim of this research is to investigate the application of open source geographic information system software, geographical resources analysis support system (GRASS) for landslide hazard assessment.